STUDENTS’ WRITING PROFICIENCY: THE TYPES OF ERRORS EXHIBITED BY STUDENTS IN THE ENGLISH COMPOSITION - M. Syafii M. Syafii; jonri kasdi; khairunnas syafii (Al-Manar : English and Arabic Journal, 2014)
This research tried to investigate three major research problems, namely: (1) the types of morphological errors based on the scope of Linguistic Category Taxonomy (LCT), (2) the types of syntactical errors based on the scope of Linguistic category Taxonomy (LCT) and (3) the types of both morphological and syntactical errors based on the scope of Surface Strategy Taxonomy (SST). There were merely 25 (30 %) of compositions were checked as the sample of 30 compositions done by the respondents. Pertaining to the performance of students in writing, especially in terms of morphology, the errors were dominated by the taxonomy of mis-formation (79 errors =75.23 %). On the other hand, in term of syntax, the errors were also dominated by the taxonomy of mis-formation (123 errors = 77.40 %).Based on the results of the research depicted above, therefore, the researcher suggests, especially to the teachers of writing to intensify the applications of peer collaborative writing, peer collaborative learning, and peer correction in ESL/EFL Writing class. Having those activities, it facilitates and enables the student writers to learn from faster student writers. Besides, it familiarizes students with tolerant and appreciative manners. Consequently, the intricate problems of writings such as limited knowledge of grammar, un-fluent and unclear ideas expressed or stated which were caused by the lack of vocabulary mastery (inadequate knowledge of vocabulary, idioms, word forms) can be minimized.